Diabetes care providers’ opinions and working methods after four years of experience with a diabetes patient web portal; a survey among health care providers in general practices and an outpatient clinic - Maaike C. M. Ronda; Lioe-Ting Dijkhorst-Oei; Rimke C. Vos; Guy E. H. M. Rutten (BMC Family Practice, 2018)
Abstract Background To gain insight into the opinions and working methods of diabetes care providers after using a diabetes web portal for 4 years in order to understand the role of the provider in patients’ web portal use. Methods Survey among physicians and nurses from general practices and an outpatient clinic, correlated with data from the common web portal. Results One hundred twenty-eight questionnaires were analysed (response rate 56.6%). Responders’ mean age was 46.2 ± 9.8 years and 43.8% were physicians. The majority was of opinion that the portal improves patients’ diabetes knowledge (90.6%) and quality of care (72.7%). Although uploading glucose diary (93.6%) and patient access to laboratory and clinical notes (91.2 and 71.0%) were considered important, these features were recommended to patients in only 71.8 and 19.5% respectively. 64.8% declared they informed their patients about the portal and 45.3% handed-out the information leaflet and website address. The portal was especially recommended to type 1 diabetes patients (78.3%); those on insulin (84.3%) and patients aged< 65 years (72.4%). Few found it timesaving (21.9%). Diabetes care providers’ opinions were not associated with patients’ portal use. Conclusions Providers are positive about patients web portals but still not recommend or encourage the use to all patients. There seems room for improvement in their working methods.